Enhanced Electrocatalytic Activity and Stability toward the Oxygen Reduction Reaction with Unprotected Pt Nanoclusters - Jing Liu; Jiao Yin; Bo Feng; Tao Xu; Fu Wang (Nanomaterials, 2018)
The Pt particles within diameters of 1⁻3 nm known as Pt nanoclusters (NCs) are widely considered to be satisfactory oxygen reduction reaction (ORR) catalysts due to higher electrocatalytic performance and cost effectiveness. However, the utilization of such smaller Pt NCs is always limited by the synthesis strategies, stability and methanol tolerance of Pt. Herein, unprotected Pt NCs (~2.2 nm) dispersed on carbon nanotubes (CNTs) were prepared via a modified top-down approach using liquid Li as a solvent to break down the bulk Pt. Compared with the commercial Pt/C, the resultant Pt NCs/CNTs catalyst (Pt loading: 10 wt.%) exhibited more desirable ORR catalytic performance in 0.1 M HClO4. The specific activity (SA) and mass activity (MA) at 0.9 V for ORR over Pt NCs/CNTs were 2.5 and 3.2 times higher than those over the commercial Pt/C (Pt loading: 20 wt.%). Meanwhile, the Pt NCs/CNTs catalyst demonstrated more satisfactory stability and methanol tolerance. Compared with the obvious loss (~69%) of commercial Pt/C, only a slight current decrease (~10%) was observed for Pt NCs/CNTs after the chronoamperometric measurement for 2 × 104 s. Hence, the as-prepared Pt NCs/CNTs material displays great potential as a practical ORR catalyst.